PENGARUH JUMLAH TANGGUNGAN, PENDAPATAN DAN BESAR PINJAMAN TERHADAP TINGKAT KELANCARAN PENGEMBALIAN KREDIT USAHA RAKYAT (KUR) MIKRO PADA BRI CABANG LARANTUKA - Koten, Veronika Loeng; Sayang, Sabulon (Program Studi Akuntansi Universitas Flores, 2022)
This study aims (1) to determine the effect of the number of dependents on the smooth rate of return of Micro People's Business Credit (KUR) at BRI Larantuka Branch. (2) to determine the effect of operating income on the smooth rate of return of Micro People's Business Credit (KUR) at BRI Larantuka Branch. (3) to determine the influence of the size of the loan on the smooth rate of return of Micro People's Business Credit (KUR) at BRI Larantuka Branch. This research is a quantitative research which is a type of research whose specifications are systematic, planned and clearly structured from the beginning to the research design. Data were collected by observation, interviews, questionnaires and literature study using multiple linear regression analysis techniques. The results of this study indicate that (1) The number of dependents has a significant effect on the level of smoothness of Micro People's Business Credit (KUR) repayments at BRI Larantuka Branch. This can be seen from the tcount > ttable (3.204 < 1.70562) with a significance level (0.004 < 0.05). (2) Income has a significant effect on the smooth rate of return of Micro People's Business Credit (KUR) at BRI Larantuka Branch. This can be seen from the tcount > ttable (2.830 < 1.70562) with a significance level (0.009 < 0.05). (3) The size of the loan has a significant effect on the level of smoothness of Micro People's Business Credit (KUR) repayments at BRI Larantuka Branch. This can be seen from the tcount > ttable (4.394 < 1.70562) with a significance level (0.000 < 0.05).